Kemampuan Mahasiswa Calon Guru Biologi dalam Merancang Pembelajaran Berbasis Praktikum: Studi Kasus Mahasiswa Pendidikan Biologi FKIP UMS - Putri Agustina; Puput Putri Kus Sundari; Dewi Eri Ardani (Universitas Sebelas Maret, 2016)
This research aimed to analyze Biology students’ pre-service teacher education ability in designing practice based learning. It was a descriptive research. Research subject were students of pre-service teacher education in Biology education department faculty of teacher training and education Universitas Muhammadiyah Surakarta (UMS) which took the PPBS course which amounted to 39 students. Data the ability of students in designing Biology practice based learning obtained from the lesson plan which was developed with the result of their trial in the classroom. Result of this research showed that most of students have been able in designing practice based learning. Lesson plan assessment results show that on average the average score is highest in recognizing aspects of laboratory equipment (78.5) while the lowest is in the planning aspects of the experimental procedure (69.5). If the views of the average total, then generally the value obtained by the students in designing lesson plan included in the category quite well (73.5). The assessment results show that the achievement of learning simulation highest value contained in readiness indicator space, tools, and media lab (77.5), while the lowest for the indicators to guide students to experiment (67.5). If seen from the average value of the overall indicator, the value of students' ability to perform simulations lesson plan included in the category quite well (71.8). The ability of students in designing the lab is one aspect of Pedagogical Content Knowledge (PCK) to be controlled by the student as a professional teacher candidates.Keywords: Biology learning, practice, lesson plan, pre-service teacher